A fast multislice sequence for 3D MRI-CEST pH imaging - Villano, Daisy; Romdhane, Feriel; Irrera, Pietro; Consolino, Lorena; Anemone, Annasofia; Zaiß, Moritz; Dastrù, Walter; Longo, Dario Livio (Magnetic Resonance in Medicine, 2020)
Purpose: Chemical exchange saturation transfer MRI can provide accurate pH images, but the slow scan time (due to long saturation periods and multiple offsets sampling) reduce both the volume coverage and spatial resolution capability, hence the possibility to interrogate the heterogeneity in tumors and organs. To overcome these limitations, we propose a fast multislice CEST-MRI sequence with high pH accuracy and spatial resolution. Methods: The sequence first uses a long saturation pulse to induce the steady-state CEST contrast and a second short saturation pulse repeated after each image acquisition to compensate for signal losses based on an uneven irradiation scheme combined with a single-shot rapid acquisition with refocusing echoes readout. Sequence sensitivity and accuracy in measuring pH was optimized by simulation and assessed by in vitro studies in pH-varying phantoms. In vivo validation was performed in two applications by acquiring multislice pH images covering the whole tumors and kidneys after iopamidol injection. Results: Simulated and in vivo data showed comparable contrast efficiency and pH responsiveness by reducing saturation time. The experimental data from a homogeneous, pH-varying, iopamidol-containing phantom show that the sequence produced a uniform CEST contrast across slices and accurate values across slices in less than 10 minutes. In vivo measurements allowed us to quantify the 3D pH gradients of tumors and kidneys, with pH ranges comparable with the literature. Conclusion: The proposed fast multislice CEST-MRI sequence allows volumetric acquisitions with good pH sensitivity, accuracy, and spatial resolution for several in vivo pH imaging applications.
CRIS-Team Scopus Importer:2020-10-16
Keywords: 3D; CEST; extracellular pH; iopamidol; MRI; RARE